Thyroid cytology—nuclear versus architectural atypia within the "Atypia of undetermined significance/follicular lesion of undetermined significance" Bethesda category have significantly different rates of malignancy. Issue 4 (13th February 2017) - Gan, Tiffany Rui Xuan; Nga, Min En; Lum, Jeffrey Huey Yew; Wong, Wendy Meihua; Tan, Wee Boon; Parameswaran, Rajeev; Ngiam, Kee Yuan
Abstract : BACKGROUND: The Bethesda System for Reporting Thyroid Cytopathology is the most widely used classification system for the reporting of thyroid fine‐needle aspiration cytology (FNAC) specimens. However, the "atypical" category ("atypia of undetermined significance" [AUS] or "follicular lesion of undetermined significance" [FLUS]) continues to cause diagnostic and therapeutic dilemmas. The objectives of this study were to describe the differential malignancy rates of FNACs diagnosed as AUS/FLUS based on nuclear or architectural atypia and to assess the significance of demographic and ultrasonographic features in predicting malignancy in this category. METHODS: A retrospective review was performed of all thyroid FNACs between 2008 and 2014 that were diagnosed as AUS/FLUS at a tertiary referral center in Singapore. Patient demographics, preoperative ultrasonographic features, and follow‐up data were collected and correlated with the final histopathologic diagnosis in resected cases. RESULTS: In total, 309 thyroid nodules were diagnosed as AUS/FLUS, and 137 (44%) were surgically excised. Final histology yielded 37 (27%) malignancies. The malignancy rate for nodules that featured nuclear atypia was significantly higher at 36.8% than the rate for nodules that had only architectural atypia at 14.7% ( P < .01). After up to 3 repeat FNACs, 67.1% of cases had a more definitive diagnosis. The only predictive sonographic finding for malignancy was irregular margins ( P < .01). CONCLUSIONS: The disparity between malignancy risks within the Bethesda "atypical" category suggests that cytologic (nuclear) atypia is significantly more predictive of malignancy than architectural atypia. This supports the substratification of patients according to risk and a corresponding management approach within this category. A sonographic finding of irregular margins is also predictive for malignancy. Cancer Cytopathol 2017;125:245–256. © 2016 American Cancer Society. Abstract : In this Singapore cohort, the malignancy rate for surgically excised thyroid nodules with a diagnosis of atypia of undetermined significance/follicular lesion of undetermined significance is 27%, and the presence of nuclear atypia yields a significantly higher malignancy rate at 36.8% than architectural atypia at 14.7%. Subclassification of the "atypical" Bethesda category should be advocated.